Indução de radiofotoluminescência em polímeros biodegradáveis e bioplásticos à base de amido natural por exposição às radiações UV e gama - Elisete Lopes da Cunha (2020)
In this work, the photoluminescent properties of biodegradable polymers and starch-based bioplastic films, radio-induced by exposure to gamma and ultraviolet UV radiation, were investigated. As well as the vast majority of organic materials, these polymeric materials initially do not have any photoluminescent characteristics. Natural starch-based biofilms made of corn, potato and cassava were produced. Solutions containing commercial starch, pure water and glycerin PA plasticizer were prepared. Film samples of Poly (butylene adipate-co-terephthalate) [PBAT], a biodegradable aliphatic-aromatic copolyester, were prepared by “casting” from trichloromethane at room temperature. The PBAT low energy UV study revealed that the irradiated films show high PL output after exposure to an 8 watts UV Fluorescent Lamp, by more than 50 h. The PL emission spectra taken during photo-excitation with a blue Led source (405 nm) revealed that the PL output yield is higher for samples irradiated under O2 rich atmosphere than in the air. The relationship between PL Intensity and Spectral Irradiance shows a linear behavior, allowing to perform 2D dosimetry in UV fields. Additionally, the PL emission’s red and blue components also have dosimetric behavior. FTIR data confirms that the mechanism behind the radio-induction of PL features by UV radiation is similar to that suggested earlier for gamma radiation, i. e. the appearing of aromatic amines during irradiation. On the other hand, the investigation of the radio-induction of photoluminescent properties in natural starch biofilms was carried out using the two radiation qualities, namely gamma and ultraviolet. Regarding gamma irradiations, the film samples were irradiated with doses ranging from 0.0 kGy to 2,100.0 kGy. For UV irradiations, the samples were irradiated with Spectral Irradiances ranging from 0.0 to 141.69 J.cm-2. Photoluminescent characteristics induced by gamma irradiation similar to those reported for PBAT were observed in the three types of starch biofilm, although with photo-emission at different wavelengths, i.e. 490 nm and 532 nm, respectively. The PL intensities observed in samples irradiated with UV radiation were much lower than those samples irradiated with gamma doses. The dosimetric relationship between PL intensity and radiation dose for the three types of starch biofilms is linear, with linear correlation factors of 0.98, 0.97 and 0.99 for potato, cassava and corn starches, respectively. Among the studied starches, it was clear that the corn starch has a photoluminescence almost 100% greater than the others. The FTIR spectra of samples irradiated with gamma and UV revealed evidences of radio-induction of aromatic amines, mainly at 1,265 cm-1, which was attributed to the stretching C-N bonds in NH2 molecules, and at 1,712 cm-1, attributed to the deformation of NH2 in primary amines. The peak intensity increase in the 3,000 to 3,600 cm-1 spectral range was attributed to the increase of OH bonds, by converting aldehydes into carboxyl groups during irradiation in the presence of oxygen. It has also been attributed to the bonding of N-H groups to the hydrocarbon or pyranose rings, identified in the FTIR spectra by the elongating vibrational modes of these bonds. The phenomenon of radio-induction of photoluminescent properties in PBAT and in the starch-based biofilms is analogous to the elsewhere well-known phenomenon of Radiophotoluminescence, observed in inorganic materials since the 1950s. The discovery of high yields of photoluminescent emission features in starchy materials opens up a wide field of applications for this class of materials, such as in high dose 2D and 3D dosimetry and also in bioimaging devices.